Airport passenger experiences in concourses with either electrochromic or low-e glass windows. (9th February 2021) - Hedge, Alan; MacNaughton, Piers; Woo, May; Guglielmetti, Robert; Tinianov, Brandon
A survey of travellers was conducted at a major US airport. A computer-based questionnaire was administered during the daytime to 573 passengers at their departure gate seating areas in either a concourse with low-emissivity glass or a newly constructed concourse with electrochromic glass. Sample sizes and characteristics were comparable for respondents in the two concourses. In the concourse with electrochromic glass, window surface temperatures were significantly cooler and more spatially consistent, and passenger comfort with daylight and positive mood were significantly better; respondents were 68% more likely to report being very satisfied with their gate experience. Overall, results agree with previous research showing that the visual environment and visual experience for airline passengers is improved by using electrochromic glass at airport gates.